Peran Teknologi Informasi dalam Pengembangan Sistem Informasi Akuntansi dalam Meningkatkan Kinerja Perusahaan: Studi Literatur tahun 2023- 2025 - Balqis Zhofayra Alya; Fauziah Hanum; Muhammad Rizal (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
The advancement of information technology (IT) has shifted accounting information systems (AIS) from administrative tools to strategic instruments that improve organizational performance. This study analyzes the role of IT in AIS development through a review of recent literature (2023–2025). The results show that integrating cloud computing, artificial intelligence (AI), big data, and blockchain enhances efficiency, transparency, and good corporate governance. Moreover, system development has moved from linear models to modern approaches such as Agile, DevOps, and Design Thinking, which are more flexible and user-centered. In conclusion, applying IT in AIS is essential for producing reliable financial information and maintaining competitiveness in the digital era